2015
DOI: 10.1155/2015/790417
|View full text |Cite
|
Sign up to set email alerts
|

Developing Pedagogical Content Knowledge: Lessons Learned from Intervention Studies

Abstract: Pedagogical content knowledge (PCK) is generally accepted as positively impacting teaching quality and student learning. Therefore, research on PCK development in (prospective) teachers is highly relevant. Based on a search in three databases (ERIC, PsycInfo, and Web of Science), a systematic review is conducted on intervention studies aiming at PCK development. The research questions are threefold: (1) How are the studies designed? (2) How are the interventions designed? and (3) What elements of interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 103 publications
1
38
2
9
Order By: Relevance
“…Although research on the effectiveness of interventions for developing teacher TPACK is limited to date, helpful starting points could be gleaned from the longer-standing body of research on PCK. In a recent review study, Evens, Elen, and Depaepe (2015) found that effective interventions for developing teachers' PCK often feature the following components: reflection, PCK courses, contact with other teachers, and experiences in educational practice. Given that the pre-service teacher educators prioritised pre-service teacher learning about the pedagogical uses of technology, this may be the most appropriate focus for reflection and redesign of teacher education courses, at least with first-and second-year students.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although research on the effectiveness of interventions for developing teacher TPACK is limited to date, helpful starting points could be gleaned from the longer-standing body of research on PCK. In a recent review study, Evens, Elen, and Depaepe (2015) found that effective interventions for developing teachers' PCK often feature the following components: reflection, PCK courses, contact with other teachers, and experiences in educational practice. Given that the pre-service teacher educators prioritised pre-service teacher learning about the pedagogical uses of technology, this may be the most appropriate focus for reflection and redesign of teacher education courses, at least with first-and second-year students.…”
Section: Future Directionsmentioning
confidence: 99%
“…Hittills har denna forskning till övervägande del handlat om den ämnesdidaktiska kunskap som behövs inom naturvetenskaps-och matematikundervisning. Endast en mycket liten andel handlar om andra ämnesområden (Evens et al 2015:3, Hashweh 2013. Begreppet ämnesdidaktisk kunskap har dock mycket att tillföra analysen av blivande och verksamma lärares kunskap om undervisning inom alla ämnesområden.…”
Section: äMnesdidaktisk Kunskapsbildningunclassified
“…• kollegialt samarbete Av dessa källor anger många forskare (exempelvis Borko & Livingston 1989;Evens et al 2015;Korthagen et al 2006;Nilsson 2008a) undervisningserfarenhet, reflektion över undervisning och samarbete med andra lärare som särskilt gynnsamma för ämnesdidaktisk kunskapsbildning. Med andra ord betonas värdet av praktiknära erfarenhet snarare än teori, vilket har betydelse för blivande lärares möjlighet att utveckla ämnesdidaktisk kunskap i lärarutbildningen.…”
Section: äMnesdidaktisk Kunskapsbildningunclassified
See 1 more Smart Citation
“…After Shulman's (1986) seminal call for a more significant inclusion of subject matter knowledge in teacher training programs, the next generation of researchers in the science teaching field expressed a concern about the abundance of training programs which do reinforce disciplinary knowledge, but without transforming it into pedagogical content knowledge (Poulson, 2001). Up to the present, efforts for adequately relating SMK and PCK are the core of a variety of teacher training programs which offer the students many possibilities to develop self-regulation in learning to teach and in teaching (Evens, Elen, & Depaepe, 2015).…”
Section: Teacher Training Programs Helping Preservice Teachers To Buimentioning
confidence: 99%